2022
DOI: 10.3390/ijms23179724
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of Human Bronchial Epithelial Cells during SARS-CoV-2 Infection: Morphological Comparison of Wild-Type and CFTR-Modified Cells

Abstract: SARS-CoV-2 replicates in host cell cytoplasm. People with cystic fibrosis, considered at risk of developing severe symptoms of COVID-19, instead, tend to show mild symptoms. We, thus, analyzed at the ultrastructural level the morphological effects of SARS-CoV-2 infection on wild-type (WT) and F508del (ΔF) CFTR-expressing CFBE41o- cells at early and late time points post infection. We also investigated ACE2 expression through immune-electron microscopy. At early times of infection, WT cells exhibited double-mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Moreover, CFTR has been implicated in cellular processes, such as apoptosis [ 46 ], carcinogenesis [ 47 ], and inflammation [ 48 ]. Research indicates its involvement in host defense against viral infections, such as SARS-CoV-2, where CFTR deficiency correlates with decreased susceptibility [ 31 , 49 , 50 , 51 ]. In this study, we compared senescence markers in WT and CFTR-knockout (KO) human bronchial 16HBE14o-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CFTR has been implicated in cellular processes, such as apoptosis [ 46 ], carcinogenesis [ 47 ], and inflammation [ 48 ]. Research indicates its involvement in host defense against viral infections, such as SARS-CoV-2, where CFTR deficiency correlates with decreased susceptibility [ 31 , 49 , 50 , 51 ]. In this study, we compared senescence markers in WT and CFTR-knockout (KO) human bronchial 16HBE14o-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CF cell lines and CFTR knockout animal studies indicate that the loss of CFTR is sufficient to generate a proinflammatory environment [ 62 ], which can lead to the ROS-mediated activation of transglutaminase-2 (TGM-2) and the inactivation of the Beclin-1 complex, resulting in autophagy impairment [ 55 , 63 , 64 ]. Since the results in mock-infected cells suggested the activation of a senescence-like pathway in CFTR-modified cells, and previously published data highlighted a low impact of SARS-CoV-2 on these cells [ 31 , 32 , 49 , 50 , 65 ], we aimed to analyze a possible interaction between senescence pathways, CFTR expression/function, and SARS-CoV-2 infection. Viral infections can trigger premature cellular senescence, known as virus-induced senescence (VIS).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of CF, reduced SARS-CoV-2 replication could depend on defective autophagosome formation (Figure 3). A recent study by Merigo et al (2022) focused on the ultrastructural analysis of bronchial epithelial cells after SARS-CoV-2 infection and reported that autophagosomes containing replicative structures were observed at a late time of infection (from 48 h post-infection). Isogenic bronchial epithelial cells expressing deficient and malfunctioning CFTRs displayed autophagosomal structures during both the early and late time of infection containing cellular recycling material, as opposed to replicative structures.…”
Section: Sars-cov-2 Infection and Cftr Protein Alterationmentioning
confidence: 99%
“…Since these processes and cellular components are altered due to impaired anions conductance in CF cells, the connection between CFTR dysfunction and DMVs alteration is highly likely. Indeed, it has been reported that CFTR-modified cells do show some differences in cellular structure compared to normal cells and once infected with SARS-CoV-2 they display an impaired organization of replicative structures (Merigo et al, 2022).…”
Section: Sars-cov-2 Infection and Cftr Protein Alterationmentioning
confidence: 99%